2003
DOI: 10.1007/s10151-003-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Conventional cutting vs. internal anal sphincter-preserving seton for high trans-sphincteric fistula: a prospective randomized manometric and clinical trial

Abstract: A larger prospective study of internal anal sphincter-preserving seton use in cryptogenic high transshincteric fistula-in-ano appears justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 30 publications
0
58
0
3
Order By: Relevance
“…Most references were retrospective studies reviewing patients' charts or prospective studies using a cutting seton, without a second treatment arm for comparison. The exceptions were Ho et al [20], Shukla et al [21] and Zbar et al [22] who reported prospective randomized trials, with at least two treatment arms.…”
Section: Cutting Setonsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most references were retrospective studies reviewing patients' charts or prospective studies using a cutting seton, without a second treatment arm for comparison. The exceptions were Ho et al [20], Shukla et al [21] and Zbar et al [22] who reported prospective randomized trials, with at least two treatment arms.…”
Section: Cutting Setonsmentioning
confidence: 99%
“…Table 4 shows the rates of incontinence after cutting seton treatment for each classification of fistula. 'Transsphincteric' includes transsphincteric, low and high, and [35] 13 ⁄ 21 Every second day Culp [26] 3 ⁄ 20 Patient moved seton several times daily Decanini-Terán et al [37] 0 ⁄ 42 Started 3 weeks postoperative; as patient tolerated Deshpande et al [30] 0 ⁄ 397 Every week Durgan et al [38] 2 ⁄ 10 Every 10 days Dziki and Bartos [39] 12 ⁄ 32 † Once a week Fasth et al [40] 0 ⁄ 7 Started a minimum of 3 months postoperative; 2-3 times weekly Flich Carbonell et al [41] 3 ⁄ 19 Not tighten postoperatively Gonzalez-Ruiz et al [43] 0 ⁄ 31 2-Week intervals Graf et al [44] 15 ⁄ 29 Once at 4 weeks postoperative Gurer et al [25] 0 [55] 0 ⁄ 53 Weekly Mohite et al [31] 0 ⁄ 114 New setons inserted weekly Qureshi et al [57] 2 ⁄ 4 Examined weekly; tightened if necessary Shukla et al [21] 8 ⁄ 155 Seton changed weekly Tahir [58] 5 ⁄ 9 Examined weekly; tightened as necessary Theerapol et al [59] 0 ⁄ 41 Patient to pull seton on a daily basis, one week postoperative Vatansev et al [61] 5 ⁄ 32 Tightened once in a period of 2 weeks Walfisch et al [62] 0 ⁄ 23 Once at 1 month postoperative Williams et al [63] 8 ⁄ 13 Patients followed regularly; tightened as necessary Zbar et al [22] 3 ⁄ 34 2-Week intervals Average rate 11.2% *Number of incidents of incontinence ⁄ number of patients.…”
Section: Classification Of Fistulamentioning
confidence: 99%
See 2 more Smart Citations
“…The data regarding deliberate IAS preservation (and repair) in high fistulas are currently too small to permit us to draw meaningful conclusions as to its significance. There were no differences between preserved and non-preserved groups in reported incontinence in a randomized controlled trial [5] although the resting pressures of the IAS-preserved group were higher than those of patients in whom it was not protected [6]. I would suggest, as Atkin and colleagues do, that IAS preservation where possible in most fistula management should be strongly recommended based on these physiological and functional observations.…”
mentioning
confidence: 94%